A study on farmers' acceptance towards biopesticides application in organic paddy farming / Ummi Kalsom Rozlan - Rozlan, Ummi Kalsom (Faculty of Plantation and Agrotechnology, 2016)
Paddy is the most important food source that consumed by 1.6 billion people in Asia. In Malaysia, paddy is considered as staple food. Pesticides is one of the important element that used by the plant to grow healthy. Synthetic pesticides are used widely for the control of various insect pests because it can be applied whenever and wherever needed, economical and most important thing is the reliability of control method. However, synthetic pesticides have also caused unprecedented ecological damage, also induced serious health hazard among workers during manufacture, formulation and field applications. To overcome the problems of synthetic hazards, one of the best control measures is the use biopesticides. However organic farmers in Malaysia especially in Besut, Terengganu area may lacks of knowledge and have different attitudes towards biopesticides application. Therefore, a research study was held at Kampung Durian Telor to evaluate farmers' acceptance towards biopesticides application. Data was collected by questionnaires form that being answered by farmers that registered under lPNT Daerah Besut. About 10 farmers or respondents were selected to answer the questionnaires. Pearson Correlation method was used to determine the relationship between independent variable which is knowledge of farmers and attitude of farmers towards biopesticides application. Multiple regression also being used to evaluate the most influence factor that influencing dependent variable. From the study, finding that have been found that independent variable have positively relationship with dependent variable. From the result also shows that knowledge is the most influencing factor that affecting farmers' acceptance towards biopesticides application.